Challenges on Diagnoses and Assessments Related to Autism Spectrum Disorder in Brazil: A Systematic Review - Sukiennik, Ricardo; Marchezan, Josemar; Scornavacca, Francisco (Frontiers in Neurology, 2022)
Background: being a continental country, with over 210 million citizens, Brazil is similar to all of those who are part of the LAMIC (Low and middle income countries). It shows a big concentration of wealth, mainly in its south and southeast regions, as well as areas with immense poverty. In that sense, the health system also faces a huge amount of contrast. Inside University hospitals and facilities there are sophisticated tools and trained doctors prepared to assist in any kind of medical subject, including autism. But, unfortunately, at other times, the access to a good health system is made much harder. This results in many issues in the medical community, for example, looking at the data regarding autism, there is a high average of the age of diagnosis. Another issue isthe low number of professionals trained in ASD diagnosis and the few tools translated to portuguese.